A Comparative Study between Factor Based Sentiment and Overall Sentiment - Modak, Santanu; Mondal, Abhoy Chand (International Journal of Computer Sciences and Engineering, 2025)
Sentiment Analysis has pulled in significantly more consideration from analysts in late years. As web based shopping is getting to be typical, more item data and item audits are posted on the Internet. Since clients can't see and feel the items straightforwardly, item surveys are turning into a basic wellspring of subjective data. Accordingly, the volume of audits is expanding drastically. It is hard to a client to peruse every one of the surveys of related item and contrast and other item in view of audits. Some of the time there is a contrast between in general assessment of the item and supposition about each feature of a similar item. In this paper, we examine 480 smart phone surveys from famous online business site and endeavor to locate a similar contrast. We allot fuzzy score for each sentiment word and figure arithmetic mean of the allocated fuzzy scores. Examination results demonstrate that connection between the general assessment and aftereffect of feature extraction undertaking , and the promising execution of our methodology has likewise been appeared.